PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP EMPLOYEE ENGAGEMENT DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (Studi pada Staf Medis Rumah Sakit Lavalette Malang) - Silvia Indra Mustika; Kusdi Rahardjo (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research aims to analyis and examine; 1) influence of perceived organizational support variable on employee engagement variable; 2) influence of perceived organizational support variable on organizational citizenship behaviour variable; 3) influence of employee engagement variable on organizational citizenship behaviour variable . The kind of research used in this research is an explanation or explanotory research with a quantitative approach. The variable in this research is perceived organizational support as independent variables and the employee engagement and organizational citizenship behaviour variable as the dependent variable. This research uses descriptve analysis and path analysis. The results of multiple linear regression analysis showed; 1) there is a significant effect between perceived organizational support variable (X) to employee engagement variable (Y1); 2) there is no significant effect between variables perceived organizational support (X) to organizational citizenship behaviour variable variable (Y2); 3) there is a significant effect between employee engagement variable (Y1) to organizational citizenship behaviour variable variable (Y2). Keyword: Perceived Organizational Support, Employee Engagement, Organizational Citizenship Behaviour. ABSTRAK Penelitian ini bertujuan untuk menganalisis dan menguji: 1) pengaruh variabel perceived organizational support terhadap variabel employee engagement; 2) pengaruh variabel perceived organizational support terhadap variabel organizational citizenship behaviour. 3) pengaruh variabel employee engagement terhadap organizational citizenship behaviour . Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian penjelasan atau explanatory research dengan pendekatan kuantitatif. Variabel dalam penelitian ini adalah perceived organizational support sebagai variabel bebas dan employee engagement serta organizational citizenship behaviour sebagai variabel terikat. Metode analisis data yang digunakan adalah analisis deskriptif dan analisis jalur. Hasil analisis jalur menunjukkan bahwa: 1) terdapat pengaruh yang signifikan anatara variabel perceived organizational support terhadap variabel employee engagement; 2) terdapat pengaruh yang tidak signifikan antara variabel perceived organizational support terhadap variabel organizational citizenship behaviour. 3) terdapat pengaruh yang signifikan antara variabel employee engagement terhadap organizational citizenship behaviour . Kata kunci: Perceived Organizational Support, Employee Engagement, Organizational Citizenship Behaviour.